(untitled) (Philological Studies, 2020)
This paper investigates the use of the present participle in English as a predicative adjunct and its Macedonian translation equivalents. The English present participle is widely used in a position after the predicate in a sentence. The research is focused on the present participle used predicatively. The research is conducted on a corpus of sentences, excerpted from English and American literature and their Macedonian translation equivalents. Consequently, comparative and descriptive methods have been used to analyze the excerpted sentences. The results show that mostly the present participle and the present participle clauses having the role of the predicative adjunct are translated into Macedonian with a verbal adverb and clauses with verbal adverb functioning as adverbial manner clauses. However, there are also examples in which the present participle is translated with a verbal adjective, also having the function of adverbial manner clauses. Besides the present participle clauses translated into Macedonian with a verbal adverb and verbal adjective there are clauses with a verb in Present, clauses with a verb in Aorist, clauses with a verb in Imperfect, clauses with da-construction, clauses with prepositional phrases and temporal adverbial clauses.